2012
DOI: 10.1002/jmri.23797
|View full text |Cite
|
Sign up to set email alerts
|

Combining MR elastography and diffusion tensor imaging for the assessment of anisotropic mechanical properties: A phantom study

Abstract: This study has demonstrated the feasibility of the proposed imaging technique for characterizing mechanical anisotropy of anisotropic materials and biological tissues, and validated the mechanical anisotropy results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 54 publications
3
107
0
Order By: Relevance
“…Similar empirical results have been shown with polyvinyl alcohol (PVA) phantoms in which a phantom was stretched and underwent multiple freeze-thaw cycles to induce anisotropy in the homogeneous material [28, 29]. Using a homogeneous phantom is much easier than embedding fibers in an external matrix [11, 15]. However, we have found that there is some residual compression that is maintained in the phantom at the end of the experiment, though this was not shown, so a particular phantom can only be used once.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Similar empirical results have been shown with polyvinyl alcohol (PVA) phantoms in which a phantom was stretched and underwent multiple freeze-thaw cycles to induce anisotropy in the homogeneous material [28, 29]. Using a homogeneous phantom is much easier than embedding fibers in an external matrix [11, 15]. However, we have found that there is some residual compression that is maintained in the phantom at the end of the experiment, though this was not shown, so a particular phantom can only be used once.…”
Section: Discussionmentioning
confidence: 56%
“…Two examples involve embedded fibers or materials in a matrix of surrounding tissue mimicking material [11, 15]. …”
Section: Introductionmentioning
confidence: 99%
“…Equation [13] invokes the incompressibility condition of Equation [6], which allowed us to neglect the z-derivative @ðr Á uÞ=@z. We note similarity to the elastic term of Equation [5] in Qin et al (33), however, with the principal difference that Equation [13] depends on three constants, whereas Qin et al reduced to two shear moduli. Our approach differs from that of Qin et al in that the element C 3333 is entirely unrelated to l 13 in accordance with the theory of elastic solids with TI symmetry.…”
Section: Shear Waves In Transversely Isotropic Mediamentioning
confidence: 86%
“…From this equation and Equation [4], the incompressible Poisson's ratios m 31 and m 12 are readily obtained by considering e 11 þ e 22 ¼ Àe 33 and e 22 þ e 33 = À e 11 corresponding to uniaxial loads along the x 3 and x 1 directions, respectively. Due to the symmetry of C of C iijj 5 C jjii , we find m ij ¼ m ji E j /E i yielding…”
Section: Theorymentioning
confidence: 99%
“…A recent study demonstrated that the acquisition of all displacement components of a multifrequency vibration is very useful for increasing the spatial resolution and the quality of MRE-derived elastograms by applying a new least square error-based reconstruction method to 3D MRE data (Hirsch et al 2013a). There have been other developments in both multifrequency and monofrequency MRE that propose the acquisition of three components of the displacement vector (Murphy et al 2011, Hirsch et al 2013b, Johnson et al 2013, Pattison et al 2010, Qin et al 2013, Hirsch et al 2013, Romano et al 2012, Yasar et al 2013a). …”
Section: Introductionmentioning
confidence: 99%